Receiving the Mute Language: How to Sound Something Which has No Name? - Dalbem, Lucas Martins (2024)
This text articulates two acousmatic situations about the language studies of the philosopher Walter Benjamin: the sound of the word and the relationship between the language of men and the language of things. Concerning this, an artistic investigation is presented involving sounds based on texts and vocal experiments that stand against the arrow of linear and empty time in the tradition of the capitalist West. Finally, it reverberates in a critical reflection on sound and listening to sound, combined with studies by sound artist Frederico Pessoa on the sounds produced in mining companies during the catastrophic extraction of minerals in the state of Minas Gerais, Brazil.